Application of phase change materials as a solution for building overheating: a case for the UK - Khalifa, Moataz (2013)
In the UK, there are about 26 million houses and the government’s future plan is to build 3 million more by 2020 (BBC, 2008, Jason, 2011). As the demand for housing increases, especially for single occupant homes, the rate of energy consumption and, in effect, the proportion of CO2 emissions is on the rise. Successful sustainable energy strategies for domestic buildings can thus be an effective tool for mitigating these effects and achieving healthy building conditions. The main aim of the research are obtaining comfortable building spaces by reducing any overheating and reduce energy demand by using passive method which also will reduce the emission of CO2. Also this work aims to raise attention on the influence of the domestic sector on the amount of CO2 emissions by using low thermal mass construction. Thus, the research’s objectives are divided into firstly, investigate the opportunity of improving the Micronal Phase Change Material (MPCM) thermal conductivity and secondly, studying the influence of using enhanced MPCM for reducing overheating in lightweight building construction. This research investigates means of improving the thermal performance of the UKs existing and new domestic buildings stock. In order to increase thermal resistance and hence reduce heat losses, a new panel comprised of outer coating and thin layer or aerogel to increase thermal resistance was developed which could be added to the exterior walls of existing houses. This research results have shown from the experimental work when MPCM coupled with construction materials that the percentage of MPCM should not be above 50% otherwise it will reduce the potential benefit of the mixture to enhance thermal conductivity of MPCM.. The best thermal conductivity was obtained by mixing 20% PCM, 75% Gypsum and 5% Silica with honeycomb, which gave a value of 0.306 W/mK. On the other hand, the best thermal conductivity was obtained using the clay by mixing 40% MPCM, 20% Clay and 40% cement, which gave a value of 0.253 W/mK. The simulation results shown that natural night ventilation could help reduce the overheating period to about 50% with the use of MPCM. Finally, The results of the new external wall panel that has been developed to improve the thermal performance have shown that through application of these panels a substantial reduction between 3 ºC to 5 ºC in the internal temperature.